2009
DOI: 10.5713/ajas.2009.80513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Qualitative and Quantitative Feed Restriction on Growth Performance and Immune Function in Broiler Chickens

Abstract: The current study was conducted to investigate the effect of early feed restriction (FR, 8 to 14 d of age) on growth performance and immune function in broiler chickens. Birds were fed corresponding diets from 3 to 35 d of age, which consisted of three phases: starter (3 to 7 d of age), FR (8 to 14 d of age) and re-alimentation (15 to 35 d of age) phases. During the FR period, each group of birds was fed the basal diet ad libitum (CON), 85% (EN85) and 70% (EN70) of lower calorie diet ad libitum (qualitative FR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
8
20
2
Order By: Relevance
“…The importance of such reserve in resisting the stresses of caloric restriction (Leveille & Sauberlich, 1961). Contrary to this finding, Jang et al (2009) found that total protein concentrations of broiler subjected to feed restrictions (70% ad libitum) from 8-14 d of age was lower than the control at 14 d of age (1.96 vs 3.26 g/dl), however, it had similar level (2.76 vs 2.12 g/dl) at the end realimentation period (35 d of age). This finding indicate that feeding time restriction had lower intensity of feed restriction, so that there was not any change reserve protein during feed restriction.…”
Section: Blood Metabolites Concentrationcontrasting
confidence: 48%
See 3 more Smart Citations
“…The importance of such reserve in resisting the stresses of caloric restriction (Leveille & Sauberlich, 1961). Contrary to this finding, Jang et al (2009) found that total protein concentrations of broiler subjected to feed restrictions (70% ad libitum) from 8-14 d of age was lower than the control at 14 d of age (1.96 vs 3.26 g/dl), however, it had similar level (2.76 vs 2.12 g/dl) at the end realimentation period (35 d of age). This finding indicate that feeding time restriction had lower intensity of feed restriction, so that there was not any change reserve protein during feed restriction.…”
Section: Blood Metabolites Concentrationcontrasting
confidence: 48%
“…These results in line with ElFiky et al (2008) that feed availability for 4 h/d with two periods of 2 h (7:00 to 9:00 and 12:00 to 14:00) decreased plasma albumin concentration of broiler (2.10 vs 2.63 g/dl) at 35 d of age. The other report, Jang et al (2009) found that plasma albumin concentrations of broiler subjected to feed restrictions (70% ad libitum) from 8-14 d of age is lower than the control at 14 d of age (0.82 vs 1.26 g/dl). Nevertheless, these findings differ with Demir et al (2004) that feed withdrawal for 16 h/d from 13-21 d of age was not influence plasma albumin of broilers at the end feed restriction (123 vs 117 g/dl).…”
Section: Blood Metabolites Concentrationmentioning
confidence: 98%
See 2 more Smart Citations
“…Most studies agree that gastrointestinal organ weight is reduced by feed restriction but is recovered by refeeding. Realimentation after feed restriction can improve feed efficiency and compensatory growth (Jang et al, 2009), and it is possible that this response can be attributed to the recovery of enzyme activity. Therefore, it is imperative to know the physiological changes that underlie feed restriction and subsequent realimentation to better understand animal nutrition and health.…”
Section: Introductionmentioning
confidence: 99%